FUTURE ENTREPRENEURS AS JOB CREATORS - IDRIS JUSOH - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
KUALA LUMPUR, 26 January 2017 Entrepreneurship is important for the future development of our beloved nation because we are aiming for education that would lead towards selfemployment. This was stated by the Minister of Higher Education, Dato' Seri Idris Jusoh at the MOHE Entrepreneurial Awards (MEA) 2016 in Kuala Lumpur, emphasising on the nurturing of future entrepreneurs to become job creators.